Wearable health trackers: A potential candidate for behavioural addiction? - Raja Babu Ramawat; Omar Afroz; Siddharth Sarkar (International Journal of Risk & Safety in Medicine, 2026)
Wearable health trackers are a type of health and fitness self-service technology that is becoming increasingly popular. Effective monitoring of health parameters offered through these devices helps in planning physical activity and weight reduction, with studies reporting their use in rehabilitation for chronic medical illnesses. However, the potential risks and harms associated with these devices remain underexplored. Apart from physical risks, such as increased risk of accidents, psychological issues related to the use of these devices include stress, guilt, low mood, and health anxiety. When criteria for behavioural addiction are applied to the use of these devices, the criteria of clinical relevance and phenomenology of use appear to be partly met, while there is a lack of data on theoretical understanding or taxonomic plausibility. We suggest that these devices be considered as a potential candidate for research on behavioural addiction. At the same time, we argue against overmedicalizing behaviours without evidence and call for a balanced approach in research to determine both the benefits and potential harms associated with wearable health trackers.